Electoral goals and center-state transfers: a theoretical model and empirical evidence from India - Wiji Arulampalam; Sugato Dasgupta; Amrita Dhillon; Bhaskar Dutta (Institute for the Study of Labor (IZA), 2008)
We construct a model of redistributive politics where the central government is opportunistic and uses its discretion to make transfers to state governments on the basis of political considerations. These considerations are the alignment between the incumbent parties at the central and state levels and whether a state is a swing state or not. A testable prediction from the model is that a state that is both swing and aligned with the central government is especially likely to receive higher transfers. We test this prediction using Indian data for 14 states from 1974-75 to 1996-97. We find that a state which is both aligned and swing in the last state election is estimated to receive 16% higher transfers than a state which is unaligned and non-swing.
Keywords: C72; 330; Redistributive politics; alignment; swing; electoral competition; Finanzausgleich; Wahlkampf; Public Choice; Indien